The Influence of Location and Village Potential on Agrotourism Development Based on Traditional Rice Farming in Pasar Melintang Village, Lubuk Pakam District - Adelina Lubis; Indah Apriliya; Wiko Rizki Wijaya; Nurul Wardani Lubis (Jurnal Mantik, 2022)
Based on its area, Pasar Melintang Village can be used as the newest tourist location on the outskirts of Medan, which offers natural views that are still beautiful, typical of the countryside, namely the concept of agro-tourism, namely traditional rice farming. Pasar Melintang Village has excellent potential to develop agro-tourism due to the available natural conditions, fertile soil conditions, and cool air climate. This is very supportive of cultivating various agricultural commodities by implementing an environmentally friendly land management system. Based on the research pre-survey conducted by researchers, the Deli Serdang area has not yet implemented the concept of agro-tourism, even though the Pasar Melintang Village area is very suitable for use as agro-tourism based on traditional rice farming because the population is dominant as a farmer. This type of research is associative, the people in this study amounted to 272 people, and the number of research samples amounted to 73 people. The kind of research data is quantitative. In this study, the researcher took the data collection technique in a questionnaire (Questionnaire), and the statistical test used was Multiple Linear Regression Analysis. Based on the partial test, it can be concluded that the location has a positive and significant effect on the development of agro-tourism based on traditional lowland rice farming in Pasar Melintang Village, Lubuk Pakam District. The village's potential has a positive and significant impact on the development of agro-tourism based on traditional lowland rice farming in Pasar Melintang Village, Lubuk Pakam District. The location and potential of the village simultaneously have a positive and significant effect on the development of agro-tourism based on traditional lowland rice farming in Pasar Melintang Village, Lubuk Pakam District